Символ. Знак. Образ - Карпенко, А.В. (Культура народов Причерноморья, 2002)
In the given article, the symbol, one of the most important concepts of the culture is being studied. The author stresses, that in spite of its importance, the problem of symbol still remains disclosed. The attempt is made to dis-tinguish the concept of symbol from the concept of sing and image.